AB0173 Mycobacterial infection in systemic lupus erythematosus: clinical significance and associated factors. data from the registry of patients with sle of the spanish society of rheumatology (RELESSER). (15th June 2017) - Pego-Reigosa, J; Campo, V; Lois-Iglesias, A; Mouriño, C; Lόpez-Longo, F; Galindo, M; Calvo, J; Ibañez, J; Olivé, A; Melero, R; FdezNebro, A; Bernal, J; et al.
Abstract : Objectives: To study the prevalence of mycobacterial infection (MI), the associated factors and their clinical significance in patients included in a large SLE cohort. Methods: Retrospective descriptive study of RELESSER patients with a history of MI and analysis of the factors associated with this infection. Results: In RELESSER 3, 658 patients with ≥4 ACR SLE criteria were included. 90% are women with a mean age of 32.9 years. 93% are Caucasians. The mean follow-up time (± SD) was 120.2 (± 87.6) months. 705 (19.3%) patients had ≥1 severe infection (defined as requiring admission); 1, 227 severe infections occurred. MI were diagnosed in 42 patients (1.2% of all RELESSER patients, 3.4% of all severe infections), 85.7% women. The incidence rate of MI was 1 per 1, 000 patients/year (95% CI:0.7–1.4). MI presentation was pulmonary in 18 (42.9%) patients and extrapulmonary in 24 (57.1%) patients [joints in 8 (19.0%) patients, soft tissue in 6 (14.3%) and other sites in 10 (23.8%)]. The extrapulmonary form was associated with immunosuppressants use: 84.6% of the 13 patients treated with immunosuppressive drugs versus 44.4% of the 27 patients without (p=0.01). We did not observe this association with the use of corticosteroids. To study the factors associated with MI, we performed a bivariate analysis including the variables associated with severe infection in RELESSER (age, sex, ethnicity, corticosteroids, immunosuppressants, antimalarials, previous admission by SLE activity, rituximab and anti-TNF use, Katz severity index, SDI index, SLEDAI index and Charlson comorbidity index). There is a statistically significant association with previous admission by SLE activity (RR:2.9, 95–95%:1.3–6.2, p=0.007), renal impairment (RR:2.0, CI 95%:1, 1–3, 7, p=0, 04), the Katz score (RR:2.1, 95% CI:1.1- 4.0, p=0.04) and the Charlson index (RR: 2.5; 95% CI: 1.3–4.8, p=0.009). Damage (SDI>0) was closely associated with significance:RR: 2.0; 95% CI: 1.0–4.0, p=0.07. Iimmunosuppressants use was associated with an important increase in the risk of MI: RR:4.3; 95% CI:2.2–8.3, p=0.31. Two patients (4.8%) died (1 respiratory and 1 extrapulmonary). Mean survival after MI diagnosis in these cases was 21 days. Conclusions: MI in RELESSER affects 1.15% of patients. Its incidence rate is 1 per 1, 000 patients/year (95% CI:0.7–1.4). Extrapulmonary localization affects more than half of the patients and is associated with immunosuppressants use. Previous admission by SLE activity, renal involvement, SLE severity and increased number of comorbidities are factors associated with MI. Acknowledgements: Work supported by Spanish Society of Rheumatology, FIS/ISCIII/FEDER (PI11/02857), BIOCAPS from the European Union 7th Framework Programme/REGPOT-2012–2013.1(316265), GSK, Roche, Novartis, UCB. Disclosure of Interest: None declared